Grazing and nutrient effects on a high rocky intertidal of the Peruvian central coast - Firstater, Fausto Nahuel (2012)
Bottom-up and top-down forces simultaneously influence benthic communities. However, their relative strength may vary with environmental conditions. In the Peruvian coast, the periwinkles are conspicuous grazers able to control both biofilm abundance and barnacle recruitment. Moreover, even in upwelling areas, algae living in the high intertidal may be nutrient-limited. Here we tested, in a nutrient-rich system, the relative effects of grazing and nutrient on the early succession of the high rocky intertidal. For this, we experimentally manipulated grazing and nutrient combined in a completely crossed design. Since nutrient and grazing seem to alter benthic community at different temporal scales, their effects were tested over the long-term (14 months) and the short-term (1 months). Over the long-term, barnacle cover increased throughout time, but was neither affected by grazing nor fertilization. At all sampling times fertilization increased biofilm cover and reduced bare rock, while exclusion of grazers also enhanced biofilm. The effect of grazing on bare rock varied through the succession. Macroalgae reached a maximum cover of 6.88%. Over the short-term, chlorophyll-a content was not affected by nutrient addition but was always higher in plots where grazer were excluded. Our results suggest that biofilm might be nutrient-limited in the high intertidal, despite being located in an upwelling area. However, the effects of grazers and nutrients on the biofilm are not reflected in macroalgae or barnacles, probably because of the occurrence of other structuring factors. In the short-term, grazing seems to have greater effect on biofilm, irrespective of the nutrient level, whereas over the longer-term, biofilm can take advantage of nutrient enhancement only in the absence of grazers.